Dynamics of Social Media on the Academic Performance of Students in Private Universities in Ghana - Okoampa-Larbi, Richard; Adu-Kumi, John; Tettey, Caroline; Amissah, Godfred; Aboagye, Solomon (International journal of education and development using information and communication technology, 2021)
In this technological era of the Internet becoming the backbone for achieving educational success, the development of social media is an asset for the academic development of students in tertiary institutions. The logit model was used to determine the dynamics of social media on the academic performance of students in private tertiary institutions in Ghana. The Statistical Package for Social Sciences and STATA were the tools employed for coding and analysis. Questionnaires were created using Google forms and administered to 900 participants. The results revealed that hours spent by students at the library have reduced drastically. It is worth noting that whether students spend less or more time on social media, their academic performance worsened. This situation was explained by students spending more time on social media for networking and not for academic purposes. Two reasons can be given for such poor performance, that is, whether students are just not able to use the social media platforms to their advantage or the platforms do not provide relevant information that can meet their academic needs. Therefore, the study concluded that Information and Communication Technology can have a lot of benefits if well managed and integrated but also on condition that a clear online policy must be established to check the conduct of students.